Crop calendar optimization for climate change adaptation in yam farming in South- Kivu, eastern D.R. Congo - Mondo, J.; Chuma, G.B.; Matiti, H.M.; Kihye, J.B.; Bagula, E.; Karume, K.; Kahindo, C.; Egeru, A.; Majaliwa, J.M.; Agre, A.P.; Adebola, P.O.; Asfaw, A. (2024)
The traditional crop calendar for yam (Dioscorea spp.) in South-Kivu, eastern Democratic Republic of Congo (DRC), is becoming increasingly inadequate given the significant climatic variability observed over the last three decades. This study aimed at: (i) assessing trends in weather data across time and space to ascertain climate change, and (ii) optimizing the yam crop calendar for various South-Kivu agro-ecological zones (AEZs) to adapt to the changing climate. The 1990–2022 weather data series were downloaded from the NASA-MERRA platform, bias correction was carried out using local weather stations’ records, and analyses were performed using RClimDex 1.9. Local knowledge and CROPWAT 8.0 were used to define planting dates for yam in different AEZs. Results showed the existence of four AEZs in the South-Kivu province, with contrasting altitudes, temperatures, and rainfall patterns. Climate change is real in all these South-Kivu’s AEZs, resulting either in rainfall deficits in some areas, or extreme rainfall events in others, with significant temperature increases across all AEZs. Suitable yam planting dates varied with AEZs, September 15th and 20th were recommended for the AEZ 2 while October 15th was optimal for AEZ 1, AEZ 3, and AEZ 4. However, none of the planting date scenarios could meet the yam water requirements in AEZ1, AEZ3, and AEZ4, since the effective rainfall (Pmm) was always inferior to the plant water demand (ETc), meaning that soil water conservation practices are needed for optimum plant growth and yield in these AEZs. This study does not recommend planting yam during the short rainy season owing to prolonged droughts coinciding with critical growth phases of yam, unless supplemental irrigation is envisaged. This study provided insights on the nature of climate change across the past three decades and suggested a yam crop calendar that suits the changing climate of eastern DRC.